Pengaruh Sistem Pengendalian Internal terhadap Siklus Pembelian Bahan Baku : (Studi Kasus pada PT Ramen Master Indonesia) - Silsy Eprillcia Florensa; Nur Ainiyah; Nurdiana Fitri Isnaini (Pajak dan Manajemen Keuangan, 2024)
The internal control system has an important role in the raw material purchase cycle in the company because the existence of an internal control system can avoid the risk of delays in the arrival of raw materials, therefore an internal control system is needed. The purpose of this study is to determine the influence of the control environment, risk assessment, control activities, communication and information as well as supervision on the raw material purchase cycle at PT Ramen Master Indonesia. The object of this research is the workforce of PT Ramen Master Indonesia Mojokerto, Surabaya Merr, Surabaya Lontar, Batu, Sidoarjo, and Gresik branches. This type of research uses a quantitative method using primary data, data analysis using SEM-PLS version 4. The results of this study are that the control environment, risk assessment, control activities, communication and information as well as supervision have a positive and significant effect on the raw material purchase cycle.